Evaluation of the effectiveness of level soil bund and soil bund age on selected soil physicochemical properties in Somodo Watershed, Jimma Zone, SouthWestern Ethiopia - Leta Hailu; Fantaw Yimer; Teklu Erkossa (Journal of Degraded and Mining Lands Management, 2020)
This study was conducted to investigate the effect of level soil bund stabilized with Vetiver grass and soil bund age on selected soil physicochemical properties on Somodo watershed, Jimma Zone, South-western, Ethiopia. A reconnaissance survey was conducted to identify a representative sampling site. From the selected sampling site croplands with level soil bund aged three years, six years and adjacent untreated cropland were identified. A total of 108 composite soil samples (3 treatments * 6 replications * 2 depths * 3 zones) were collected. Soil samples were analyzed following standard laboratory analysis. Ages of level soil bund (LSB) significantly affected SMC (soil moisture content) (p<0.01), BD (bulk density) (p<0.01), and SOC (soil organic carbon) (p<0.01). Zones showed significant difference in sand content (p<0.05), SMC (p<0.01), BD (p<0.05) and SOC (p<0.01). Moreover, the soil depths also significantly influenced silt content (p<.05), SMC (p<.01), BD (p<0.01), SOC (p<0.01), TN (total nitrogen) (p<0.01), Av.-P (available phosphorous) (p<0.01) and CEC (p<0.05). The interaction effect of the age of LSB with zone was significant for SOC (P<0.05). To sum up, the effect of the constructed level soil bund had a positive impact on selected soil physicochemical properties of the site. Therefore, the study suggests that it is essential to maintain the structure to sustain the effectiveness and scale up the technology to other watersheds with similar agroecology of the country. Further study is encouraged to understand more about the effect of the slope and Vetiver grass bund stabilization role independently on selected soil properties.